2024
DOI: 10.1097/md.0000000000037325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the problem-solving performance of ChatGPT-3.5, ChatGPT-4, Bing Chat, and Bard for the Korean emergency medicine board examination question bank

Go Un Lee,
Dae Young Hong,
Sin Young Kim
et al.

Abstract: Large language models (LLMs) have been deployed in diverse fields, and the potential for their application in medicine has been explored through numerous studies. This study aimed to evaluate and compare the performance of ChatGPT-3.5, ChatGPT-4, Bing Chat, and Bard for the Emergency Medicine Board Examination question bank in the Korean language. Of the 2353 questions in the question bank, 150 questions were randomly selected, and 27 containing figures were excluded. Questions that required abilities such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…All authors only compared the most popular chatbots, which, in most cases (except ChatGPT-4.0 and Bing Chat), use different language models. In four out of five articles, authors indicated that Bard received the lowest score [22,23,25,26]. Only in one article related to medicine did Bard receive the highest score [24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…All authors only compared the most popular chatbots, which, in most cases (except ChatGPT-4.0 and Bing Chat), use different language models. In four out of five articles, authors indicated that Bard received the lowest score [22,23,25,26]. Only in one article related to medicine did Bard receive the highest score [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, in Plevris et al, (2023) study [22], authors indicated that giving Internet access to the chatbot can provide more precise answers, particularly if these questions are available in open access. Furthermore, it was found that ChatGPT-4.0, using its LLM model, was more accurate than Bing Chat [23].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation